Do you know the biological nomenclature? Learn the correct way to write the names of organisms (Research, Society and Development, 2022)
Currently, the nomenclature of living beings is governed by international codes that are built collectively, involving the scientific community. These constructions serve to organize the nomenclature of the past and to stabilize the names of the species, with each code being independent and autonomous. Proper use, knowledge and consultation of codes make the use of nomenclatures more uniform, thus avoiding ambiguities and its uses, since proper use makes the work more uniform and unambiguous. The methodology for composing all the information referring to the spelling of the names of the organisms was made by direct consultation: International Code of Nomenclature for Algae, Fungi and Plants; International Code of Nomenclature for Cultivated Plants; International Code of Phytosociological Nomenclature; International Code of Zoological Nomenclature; International Code of Prokaryote Nomenclature; International Code of Classification and Nomenclature of Viruses; International Code of Phylogenetic Nomenclature. The absence or superficiality of nomenclatural discussions of living (or extinct) organisms in undergraduate courses at Brazilian universities (there are few exceptions) contributes to the ignorance of the existence of nomenclature codes. Examples and elucidations were presented on the correct use of nomenclatures, as well as the description of a new status (unclassified), new subdivision, and new class for plants.